Three questions on imagery and perception: A comment on Nanay's Mental imagery - Van Leeuwen, Neil (Mind & language, 2025)
Some parts of Bence Nanay's view of the relationship between mental imagery and perception appear iconoclastic. Other parts appear traditionalist. This commentary on his recent book Mental imagery poses three questions that put pressure on the idea that the iconoclastic parts and the traditionalist parts can coexist harmoniously.